Kenya today breaking the yoke of colonialism in Africa - Mwaura, Ndirangu (Algora Pub., 2005)
"Examining the impact of foreign aid, trade policies, study-abroad programs, religion, entertainment, the media and other forms of foreign influence on Kenya and other under-developed African nations, the author finds that initiatives billed as "assistance" in many cases serve instead to keep in place the colonial status of dependency"--Provided by publisher.